Excessive fluid resuscitation is associated with intensive care unit mortality in Pakistani patients with dengue shock syndrome - Moiz Salahuddin; Rameesha Khalid; Sadaf Hanif; Filza Naeem; Rameen Aijaz; Akbar Shoukat Ali (Acute and Critical Care)
Background The mortality of severe dengue infections is approximately 23%. In the management of dengue shock syndrome (DSS), aggressive fluid resuscitation is recommended. The primary objective of our study was to assess the factors associated with 30-day mortality in DSS patients. Methods Adult patients >18 years old, who were admitted with DSS were included. DSS was diagnosed in patients who required vasopressors or had lactic acidosis >4 mmol/L. Patients were divided into three different groups based on cumulative fluid balance at death or extubation: group I (<3.5 L), group II (3.5–8.0 L), and group III (>8.0 L). Results A total of 135 patients with DSS was included, with an overall 30-day mortality of 74.8%. The average Sequential Organ Failure Assessment (SOFA) score on intensive care unit admission was 12.2. Mechanical ventilation was required in 112 patients (83.0%), with 61 patients (45.2%) being intubated without a noninvasive ventilation trial. Respiratory failure was the most common reason for requiring intubation (65 patients, 48.2%). In survivors, the median cumulative fluid balance was 1,493 ml (interquartile range [IQR], 0–4,501 ml), whereas that in the mortality group was 7,797 ml (IQR, 3,700–13,600 ml). On multivariate analysis, SOFA score (odds ratio [OR], 1.220; 95% CI, 1.011–1.472; P=0.038) and having received >8.0 L cumulative fluid balance (OR, 6.682; 95% CI, 1.808–24.689; P=0.004) were associated with increased risk of mortality. Conclusions DSS patients have high mortality rates. High SOFA scores and >8.0 L cumulative fluid balance may indicate worse outcomes.